If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 129 = 0 Reorder the terms: 129 + 3x = 0 Solving 129 + 3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-129' to each side of the equation. 129 + -129 + 3x = 0 + -129 Combine like terms: 129 + -129 = 0 0 + 3x = 0 + -129 3x = 0 + -129 Combine like terms: 0 + -129 = -129 3x = -129 Divide each side by '3'. x = -43 Simplifying x = -43
| -7y=-21+28 | | 1/2(x-5)=x-2 | | 4x+3/-5x-3=-1/2 | | 6v-5+5=6v | | (2x^2+6x-7)+(4x^2+2x+17)-(6x^2-11)= | | -4(4-7b)-3(4b-6)=-30 | | 6(x-2)-2x=-40 | | -147=-7(3-3r) | | A=3X(-1) | | 1+5m+7=-7 | | t*-1.5=8 | | -4*-1.5=6 | | -8(p-5)=109.6 | | 4-3x=4(3-x)-3x | | -0.1875*8=-1.5 | | (x^2+5x+5)-(5x^2-8x+7)= | | 8*t=-1.5 | | -4.45-2=-5.5s-4.2 | | -7k-5(-7k+7)=-3+4(7-8k) | | 6*t=-9 | | 6*(-9)=t | | -(h+7)=-8 | | 12-4n=-(n+1)-5 | | (12y+14)+(-2y-3)= | | x/3+18=44 | | 10+x+5x=7x+2 | | 2x+33-5x=3-7x+2 | | (9x-1)-(4x+3)= | | 31=7(-5n-7)-4(2-6n) | | 3x^2-6x-(2-k)=0 | | .03y+.09(50000-y)=2490 | | (2x+5)+(4x-11)= |